Explaining suicide : patterns, motivations, and what notes reveal - Meyer, Cheryl L.; Irani, Taronish; Hermes, Katherine A.; Yung, Betty (Academic Press, 2017)
The rate of suicides is at its highest level in nearly 30 years. Suicide notes have long been thought to be valuable resources for understanding suicide motivation, but up to now the small sample sizes available have made an in-depth analysis difficult. Explaining Suicide: Patterns, Motivations, and What Notes Reveal represents a large-scale analysis of suicide motivation across multiple ages during the same time period. This was made possible via a unique dataset of all suicide notes collected by the coroner's office in southwestern Ohio 2000-2009. Based on an analysis of this dataset, the book identifies top motivations for suicide, how these differ between note writers and non-note writers, and what this can tell us about better suicide prevention. The book reveals the extent to which suicide is motivated by interpersonal violence, substance abuse, physical pain, grief, feelings of failure, and mental illness. Additionally, it discusses other risk factors, what differentiates suicide attempters from suicide completers, and lastly what might serve as protective factors toward resilience. Analyzes 1200+ suicide cases from one coroner's office Identifies the top motivations for suicide that are based on suicide notes Discusses the extent to which suicides are impulsive vs. planned Leads to a better understanding on how to prevent suicide Emphasizes resilience factors over risk factors.